A scenario simulation approach for sustainable mobility project evaluation based on fuzzy cognitive maps. (2nd October 2018) - Awasthi, Anjali; Omrani, Hichem
Abstract: Sustainability evaluation of new urban mobility projects is a challenging decision due to the presence of multiple objectives (social, economic, environmental), limited data availability, presence of multiple stakeholders, and specific context of each city. Scenario modeling and simulation is a useful tool to address such situations. In this paper, we present a fuzzy cognitive mapping-based scenario simulation approach for evaluating sustainable mobility projects. Linguistic assessments and fuzzy set theory are used to address the uncertainty arising from lack of quantitative data. The criteria for sustainability evaluation are obtained using fuzzy Delphi technique. A numerical application is provided for the city of Luxemburg. The strength of the proposed approach is the ability to aid in decision-making of new sustainable mobility project evaluation and selection under limited or no quantitative data availability. In addition, it is able to deal with multiple, co-related and conflicting criteria in evaluation.